Integrasie of transformasie? 'Geloof en wetenskap' of 'gelowige wetenskap' as vertrekpunte vir integrale Christelike wetenskapsbeoefening - Walt, Barend Johannes van der (Koers, 2005)
Integration or transformation? 'Faith and scholarship' or 'faith-directed scholarship' as starting-point for integral Christain scientific endeavour To be discussed in this article is the question whether the contemporary model of integration can be accepted as a valid way towards genuine Christian scholarship. To find an answer to this problem, the following steps are taken. In the introduction attention is asked for the present popularity – overseas as well as in South Africa – of this model of “faith and science”. Subsequently, the meaning of “integration” as viewed by its proponents is explained. In the following section different arguments are advanced against the integration model. The conclusion is that such a model for Christian scientific endeavour should not be regarded as the ideal. In the case of the alternative, viz. integral Christian scholarship, Christian belief is not merely tagged on to “standard” science. The contents of the different disciplines should be transformed in the light of God’s revelation, a Christian worldview, a Christian philosophy, subject philosophy and subject theory.